2022
DOI: 10.1186/s13102-022-00469-3
|View full text |Cite
|
Sign up to set email alerts
|

What are gender differences in lower limb muscle activity during jump–landing tasks? A systematic review and meta-analysis

Abstract: BackgroundGender differences in muscle activity during landing have been proposed as a possible contributing factor to the greater incidence of anterior cruciate ligament injuries in women. Conflicting results among a few studies in this regard makes it impossible to reach correct conclusions.ObjectivesThe aim of this study was systematic review and the meta-analysis of previous studies which have compared the electromyographic activity of lower limb muscles in gluteus muscles (maximus and medius), quadriceps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…There is renewed interest in understanding sex differences and similarities in skeletal muscle (SM) and body composition 1–5. On the one hand, SM is now known to be important in many physiological and disease processes 6–12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is renewed interest in understanding sex differences and similarities in skeletal muscle (SM) and body composition 1–5. On the one hand, SM is now known to be important in many physiological and disease processes 6–12.…”
Section: Introductionmentioning
confidence: 99%
“…There is renewed interest in understanding sex differences and similarities in skeletal muscle (SM) and body composition. [1][2][3][4][5] On the one hand, SM is now known to be important in many physiological and disease processes. [6][7][8][9][10][11][12] On the other hand, sports performance differences between male and female athletes have attracted new attention in recent years because of the inclusion of transgender athletes in female competitions.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on gender, the lower extremity constitutes almost 3 times the total body mass as the upper extremities. 76,77 Lower extremity amputees experience diminished cardiac contractility, work capacity, movement capabilities, and maximal oxygen intake, attributed to a significant loss of body mass, suggesting a potential impact on their cardiovascular and respiratory function. 78 To maintain hemodynamic stability, the surgical team must exercise heightened caution and meticulous attention to details when it comes to resuscitative measures, including monitoring blood pressure, assessing coagulation indicators, and administering blood product transfusions.…”
Section: Hemodilution Third-spacing and Other Hemodynamic Considerationsmentioning
confidence: 99%
“…In terms of volume, muscle mass, etc, the lower extremity's anatomical compartments differ significantly from those of the upper extremity. Depending on gender, the lower extremity constitutes almost 3 times the total body mass as the upper extremities 76,77 . Lower extremity amputees experience diminished cardiac contractility, work capacity, movement capabilities, and maximal oxygen intake, attributed to a significant loss of body mass, suggesting a potential impact on their cardiovascular and respiratory function 78 .…”
Section: Challenges In Lower Extremity Transplantationmentioning
confidence: 99%
“…Furthermore, it has been suggested that before IGC, preactivation of the knee joint agonist and antagonist muscles leads to increased joint stiffness, which can provide greater knee joint stability and protection against a noncontact ACL episode [22,40]. On the contrary, during jump landing, researchers have suggested that increased joint stiffness may reduce GRF absorption [34]; preactivation of the knee joint agonist and antagonist muscles led to a high quadricep: hamstring (Q: H) ratio (mainly due to decreased activation of the hamstrings), which was negatively correlated with the knee flexion angle at IGC [46], which reduces the force threshold required to rupture the ACL [34,41].…”
Section: Introductionmentioning
confidence: 99%